Streamlining influence on the long-haul trucks with an installed movable roof fairing performance properties teoretical studies - Virchenko, Viktor; Skoryk, Maxym; Kryvorot, Anatolii; Meshko, Oleksandr (Academic journal Industrial Machine Building Civil Engineering, 2018)
Influence streamlined elements located on the roof of the tractor main train such as the efficiency of the vehicle with installed no bonnet on it an advanced roof rack, which has the ability to adjust to any trailed warehouse. It has been assumed that it provides high levels of accuracy with respect to analogues due to the possibility of choosing the appropriate geometric parameters, provides ease of use and the ability to adjust the cushion during vehicle movement, prevents probable malfunctions during strong winds or hurricanes due to the strength of the drive management and modern electronic systems mechanical design. On the basis of theoretical studies of the main motor trains various tractors flow, the dependences of power and fuel consumption on the air traffic vehicle coefficient have been established at its movement speeds. It has been proven that it is advisable to use an advanced racing hub on precision drum trucks with small and medium-height cabs.
Keywords: main motorway; streamlined; aerodynamic properties; roof fenders; streamlining coefficient